Identification of SNPs and Candidate Genes Associated with Salt Stress in Two Korean Sorghum Cultivars and Understanding Selection Pressures in the Breeding Process - Donghyun Jeon; Solji Lee; Sehyun Choi; Yuna Kang; Changsoo Kim (Agronomy, 2022)
One of the abiotic stresses, salt stress, has an impact on the production and development of crops around the world. Sorghum is a functional genomics model crop of C4 plants due to its small genome size, and it is suitable for providing a clue to the mechanism associated with salt tolerance at the transcriptomic level. However, the mechanism of salt-related genes in sorghum has not been well described. RNA sequencing, using QuantSeq, was performed on two Korean cultivars, ‘Sodamchal’ and ‘Nampungchal’, which are known to have different intensities in response to salt stress, between a control and high-salinity treatment over a different time-course. In addition, physiological responses such as the proline, anthocyanin, chlorophyll, and reducing sugar contents were evaluated under the salt-stress treatment between these two sorghum cultivars. Moreover, differentially expressed genes (DEGs) between the Nampungchal and Sodamchal cultivars were identified in their leaves and roots, respectively. Moreover, the function of DEGs was confirmed through GO classification and KEGG pathway. We also analyzed the correlation between the selection pressure with DEGs by identifying Ka/Ks of DEGs. In the breeding process, the role of positive or negative selected genes was analyzed. Therefore, a new hypothesis on selection pressure was proposed from the breeding perspective of cultivars. A comparative analysis of the two sorghum cultivars provides candidate genes involved in the salt-stress response and may offer a better understanding of the salt-tolerance mechanism in sorghum.